122 Head Injury discharge advice in an emergency department. Issue 6 (27th May 2022) - Elkommos, Samia; Hardy, Jean; Elliot, Katherine; Jenkins, Peter; Dilley, Michael; Griffin, Colette
Abstract : Background: Head Injury (HI) is a common presentation to the Emergency Department (ED). Most injuries are mild and patients are often discharged directly from ED. However, persistent symptoms and failure to return-to-work are common. Comprehensive advice and a clear pathway if symptoms persist are critical to prevent unnecessary morbidity. Objectives: To audit the discharge advice and follow-up of patients discharged from an ED with a HI. Methodology: A Data Collection Tool was used to audit the advice and follow-up guidance given to patients attending St George's Hospital ED in December 2018 with a HI. Data was audited against the NICE Guidelines for Head Injury: Assessment and Early Management (CG176). Results: 149 patients were identified. 41 (27.5%) were provided with written advice; 53 (35.6%) had no documentation of any HI advice being given; 55 (36.9%) had some documentation of HI advice but no documentation that written material was provided. Conclusions: A need for improvement in the quality of HI Discharge Advice from ED and access to spe- cialist HI outpatient assessment was identified. Improvements implemented included education of ED staff, new patient information sheet, and direct referral system to a specialist HI clinic. Re-audit is planned following these improvements. Samia.Elkommos@nhs.net